Combination of Remdesivir, Corticosteroid, and Convalescent Plasma for Severe COVID-19 in Periviable Pregnancy. Issue 6 (November 2020) - Lam, Helena; Lacasse, Alexandre
Abstract : Abstract: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may lead to a disease spectrum named COVID-19, including a severe form of pneumonia characterized by an intense inflammatory response similar to acute respiratory distress syndrome. Current management guidelines in pregnancy have been limited. In the setting of severe COVID-19 in pregnancy, including in the periviability period, combination multitargeted therapy should be strongly considered. We report a case of severe COVID-19 pneumonia in a periviable pregnancy treated with concurrent combination of remdesivir, corticosteroids, and convalescent plasma therapy, leading to rapid maternal pulmonary improvement.